Linkages between hydrothermal alteration, natural fractures, and permeability: Integration of borehole data for reservoir characterization at the Fallon FORGE EGS site, Nevada, USA. (January 2021) - Kraal, Kurt O.; Ayling, Bridget F.; Blake, Kelly; Hackett, Logan; Perdana, Tito Satria Putra; Stacey, Robert
Highlights: The Fallon site in the western USA is evaluated for EGS potential. Petrographic, XRD, hyperspectral, geophysical and well log data are used. Natural fractures are oriented NNE-SSW, subparallel to the interpreted SHmax . Mud loss locations suggest some zones have relatively-higher permeability. Injection test results indicate an injectivity index of 0.025 L/min/kPa. Abstract: Between 2015 and 2018, the Fallon FORGE EGS (Engineered or Enhanced Geothermal System) site in Churchill County, Nevada, USA, underwent detailed geoscientific characterization to evaluate its suitability to operate as a field demonstration site to test and develop EGS technologies. This included the compilation, synthesis and acquisition of geophysical, geological, geochemical, hydrological, down-hole log, and mineralogy datasets. Site activities culminated in the drilling of a 2481 m-deep EGS observation well (21−31) to further verify the geology and rock properties of the proposed EGS reservoir formations, which are older than the Miocene and include felsic intrusions, felsic volcanics, and meta-sedimentary lithologies. In this paper, we integrate and evaluate borehole data from well 21−31, including drill cuttings and sidewall cores (petrographic, XRD, hyperspectral), wireline geophysical logs (e.g., gamma, neutron porosity, resistivity, sonic scanner), borehole imagers (FMI, BHTV), and pressure and temperature logs. Hydrothermal alteration and veining is found throughout the entire pre-Miocene interval of well 21−31, and includes epidote mineral assemblages that suggest past temperatures >250 °C. This is higher than the hottest measured equilibrated temperature at similar depths in other wells on the FORGE site today, and suggests that the system was higher temperature in the past. Overall lithologic variability is high, with volcanic, intrusive, metamorphic, and sedimentary rocks present in the bottom 700 m of the well. Natural fractures are abundant throughout the pre-Miocene section, but are more frequent in the felsic intrusive and felsic volcanic lithologies. The dominant orientation of these natural fractures observed in FMI logs is NNE-SSW with an average strike of 010° ± 40°, subparallel to the interpreted SHmax orientation of 009° ± 14° that is indicated by drilling-induced structures in the wellbore in the BHTV log. Therefore, natural fractures appear optimally oriented for reactivation via hydraulic stimulation. Mud loss locations and a non-equilibrated temperature log suggest that there are some zones with relatively-higher permeability and/or open fractures. However injection test results indicate an injectivity index of 0.025 L/min/kPa, which is an order of magnitude lower than a typical threshold for commercial wells. Analytical modeling of injection test results indicate that the majority of the well is low permeability (< 10 −16 m²), with some discrete, localized zones of higher permeability (∼ 10 -12 m², less than 0.5 percent of the pre-Miocene (deep) section intersected by the well).